Beta-adrenoblockers in clinical practice: is there any difference? - D. V. Nebieridze; A. Meliya; G. R. Kulieva (Кардиоваскулярная терапия и профилактика, 2007)
Modern views on various β-adrenoblockers (BB) place in clinical practice are presented. BB class is a clinically heterogeneous group. Recent criticism of BB should not disorient practitioners, who must understand which BB are mentioned. Some BB, mostly non-selective, demonstrate adverse effects and cannot be used in certain clinical situations: metabolic disturbances, chronic obstructive pulmonary disease (COPD), peripheral artery atherosclerosis. At the same time, modern super-selective BB are safe and can be administered even in individuals with metabolic syndrome, diabetes mellitus, COPD, or peripheral artery atherosclerosis.